Is China fudging its figures? Evidence from trading partner data - John Fernald; Eric Hsu; Mark M. Spiegel (Bank of Finland, Institute for Economies in Transition (BOFIT), 2015)
How reliable are China's GDP and other data? We address this question by using trading partner exports to China as an independent measure of its economic activity from 2000–2014. We find that the information content of Chinese GDP improves markedly after 2008.We also consider a number of plausible, non-GDP indicators of economic activity that have been identified as alternative Chinese output measures. We find that activity factors based on the first principal component of sets of indicators are substantially more informative than GDP alone. The index that best matches activity in-sample uses four indicators: electricity, rail freight, an index of raw materials supply, and retail sales. Adding GDP to this group only modestly improves in-sample performance. Moreover, out of sample, a single activity factor without GDP proves the most reliable measure of economic activity.
URN:NBN:fi:bof-201511031430
Keywords: C53; C82; E20; F17; 330